2011
DOI: 10.3171/2011.6.spine11163
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a femoral nerve motor branch for transfer to the pudendal nerve for restoring continence: a cadaveric study

Abstract: Object Nerve transfers are an effective means of restoring control to paralyzed somatic muscle groups and, recently, even denervated detrusor muscle. The authors performed a cadaveric pilot project to examine the feasibility of restoring control to the urethral and anal sphincters using a femoral motor nerve branch to reinnervate the pudendal nerve through a perineal approach. Methods Eleven cadavers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…In addition, our cadaver studies showed feasibility of the use of motor branches of the femoral nerve as a donor nerves for bladder and urethra reinnervation in humans. 11, 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our cadaver studies showed feasibility of the use of motor branches of the femoral nerve as a donor nerves for bladder and urethra reinnervation in humans. 11, 22 …”
Section: Discussionmentioning
confidence: 99%
“…Ten dogs underwent left FNT to the bilateral vesicle branches of the PN (Fig. 1C) as described 7, 11 without nerve cuff electrodes; 5 with (FNT-V) and 5 without vesicostomies (FNT-NV).…”
Section: Methodsmentioning
confidence: 99%
“…Over the past two decades, a variety of nerve transfer procedures have been designed to improve function following nerve loss with the upper and lower extremities, as well as the brachial plexus; however the use for sacral nerve root reconstruction have not been reported . Recently, the obturator nerve has been identified as a distal donor nerve for neurotization of the femoral nerve within the leg; however its use within the pelvis has not been examined .…”
mentioning
confidence: 99%
“…18, 33 In the cadavers, we exposed branches of the femoral nerve to the vastus medialis and intermedialis muscles using an anterior thigh approach. Then, the pudendal nerve was exposed in the Alcock (pudendal) canal using a perineal approach, before transferring the femoral nerve branches medially and superiorly to the pudendal nerve.…”
Section: Strategies For Bladder Reinnervationmentioning
confidence: 99%
“…Then, the pudendal nerve was exposed in the Alcock (pudendal) canal using a perineal approach, before transferring the femoral nerve branches medially and superiorly to the pudendal nerve. 18 …”
Section: Strategies For Bladder Reinnervationmentioning
confidence: 99%